Trends in the Management and Development of Complex Systems: Enhancing Productivity and Quality with Cobots Equipped with Part recognition Cameras (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article explores the emerging trends in the management and development of complex systems, with a specific focus on joint assembly processes. The study delves into the characteristics of complex systems within the context of joint assembly, analyzes engineering work and production process management methods, and highlights the essence of a synergistic approach in integrating different production standards. Furthermore, it proposes the use of collaborative robots (cobots) equipped with part detection cameras as a means to improve productivity and quality in joint assembly operations. By leveraging defect analysis techniques and integrating industry standards, this approach aims to optimize efficiency, reduce errors, and enhance overall system performance.